Semantic Interoperability Middleware – Enabling collaborative networks in public sector - Sanchez, Alejandro (2008)
Electronic Government initiatives, such as seamless public services delivered at one-stop government portals, require establishing collaborative networks among public- and private-sector organizations. However, semantic interoperability problems emerge as these organizations may differ in the terms and meanings they use to communicate, express their needs and describe resources they make available to each other. This paper describes typical semantic interoperability problems and presents a middleware solution to address them, called Semantic Interoperability Middleware (SIM). The paper illustrates the problems through three case studies in a collaborative network for the delivery of welfare benefits. Subsequently, the requirements for SIM are presented, and the architecture and design of the solution are specified using UML. SIM assumes organizations have agreed on ontologies that reflect the meaning of terms they use in communicating. It comprises three services: Mediation – resolves differences in terms and meaning; Validation – detects inconsistent terms and meaning; and Discovery – mediates and matches need with resource descriptions. Finally, the case studies are resolved applying SIM.